Fournier's Gangrene in 21 Years Old Female: A Case Report - Liwanto, Michael Adriel (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Fournier's gangrene, also known as gangrene of the genital region, is an uncommon and rapidly advancing form of necrotizing fasciitis that affects the genitals. The severity and mortality of the disease are dependent upon the overall health status of the patient at the time of diagnosis and the speed at which the infection spreads. Case presentation: An unmarried 21-year-old woman presented with a persistent discharge of abscesses in the perineal area. The patient came in ambulatory and showed no indicators of heart or lung discomfort. A pelvic examination was performed, and the following observations were made: A visual examination revealed swelling in the vulvar area on both sides, along with an open wound within the swelling measuring 3×3 cm. The wound was discharging reddish, thick, and foul-smelling fluid. A glucose level of +4 was observed in the urine, and a random blood sugar test yielded a value of 324 mg/dl. The patient received wound debridement, excision, and electrocauterization of genital warts, blood sugar monitoring with insulin administration, and a 14-day course of antibiotics. The patient's condition improved, and they were discharged after receiving 14 days of intravenous antibiotic treatment. Conclusion: The treatment of Fournier gangrene requires a comprehensive approach that includes intensive systematic management, broad-spectrum antibiotic therapy, and early surgical debridement. This involves removing the necrotic tissues and surgically draining the peritoneum, scrotum, penis, and inguinal regions.